2014
DOI: 10.1021/ct500703q
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Density Functionals for Clusters of Late Transition Metals: Assessing Energetic and Structural Properties

Abstract: We present the first application of hybrid density functional theory (DFT) methods to larger transition-metal clusters. To assess such functionals for this class of systems, we compare the performance of three modern hybrid DFT methods (PBE0, TPSSh, M06) and their semilocal counterparts (PBE, TPSS, M06L) regarding average bond distances and binding energies per atom for a series of octahedral model clusters Mn (M = Ni, Pd, Pt; n = 13, 38, 55, 79, 116). With application to large particles in mind, we extrapolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(75 citation statements)
references
References 79 publications
5
70
0
Order By: Relevance
“…[37][38][39][40][41][42] To conrm our choice of functional and basis set, the possible structures for Au 3-10 were optimized and shown in Fig. S1.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40][41][42] To conrm our choice of functional and basis set, the possible structures for Au 3-10 were optimized and shown in Fig. S1.…”
Section: Resultsmentioning
confidence: 99%
“…27,38 The possible effects of different mixing percentage of HF potential of the sX and HSE06 still cannot be ruled out. In terms of pure metal surfaces, Soini et al 56 found that the smaller HF mixing percentage in the TPSSh hybrid functional, compared with 20% HF in B3LYP and 25% HF in PBE0, offers a reasonable compromise between the self-interaction corrections and static correlation that it yields an overall good description of the late transition metal clusters. In terms of CO adsorbate on Pt(111) surface, Ref.…”
Section: -9mentioning
confidence: 99%
“…6,[15][16][17] The economical relevance 18 of industrial applications represents an especially strong driving force for scientific research aiming at a detailed understanding of the properties of TM clusters and NPs. 3,[38][39][40][41][42][43][44][45][46][47][48][49][50][51] Indeed, the physical and chemical properties of such systems follow scaling laws as they slowly approach their corresponding bulk limits. 16,[19][20][21][22][23][24] In such combined studies the experimentally examined systems need to be as close as possible to the models used in the corresponding computational studies.…”
Section: Notker Röschmentioning
confidence: 99%
“…Often enough, synergy effects resulting from joint experimental and computational studies turn out to be essential for gaining insights at the atomic level. 3,[39][40][41][42][43][44][45][46][47][48][49][50][51] The onset of this latter scaling behavior, hence the beginning of the so-called scalable regime, is smooth and the cluster sizes at which it occurs depend on the atomic element of the particles at hand and the property under study. With regard to nanocatalysis 6,[25][26][27] this requirement can impose considerable problems as the catalytically active species employed in industrial processes often are significantly larger than the computational models for which accurate calculations are feasible, 24,25 e.g., by means of Kohn-Sham (KS) density functional theory (DFT).…”
Section: Notker Röschmentioning
confidence: 99%
See 1 more Smart Citation